Algorithmic Governance and the Rule of Law: Statutory Foundations of Indonesia’s National Single Social and Economic Data (DTSEN) - Tedi Supardi Muslih; Suparmo (Jurnal Sosial Teknologi, 2026)
The background of this study is rooted in the digital transformation of Indonesian public administration, specifically the implementation of the National Single Social and Economic Data (Data Tunggal Sosial Ekonomi Nasional or DTSEN) under Presidential Instruction (Instruksi Presiden or Inpres) No. 4 of 2025. While DTSEN aims to eliminate structural inefficiencies and targeting errors in social welfare programs through advanced algorithmic data integration, its current legal foundation presents significant challenges to the rule of law. The purpose of this research is to critically analyze the statutory deficiencies arising from reliance on a Presidential Instruction for highly consequential algorithmic governance and to propose a more robust statutory framework through a comprehensive Law (Undang-Undang) or a Government Regulation in Lieu of Law (Peraturan Pemerintah Pengganti Undang-Undang or Perpu). The methods employed involve a normative-doctrinal legal approach complemented by targeted socio-legal case mapping, drawing extensively on recent literature indexed in Scopus and Sinta 2. The results indicate that Inpres No. 4 of 2025 lacks sufficient binding regulatory authority to mandate regional budget allocations, enforce public data compliance, or provide adequate administrative due process protections for citizens misclassified by automated Proxy Means Testing (PMT) algorithms. Furthermore, the absence of algorithmic accountability mechanisms creates tensions with Indonesia’s Personal Data Protection framework. The conclusion of this study is that a statutory upgrade represents a constitutional necessity. Establishing a Perpu or Law is required to bridge the gap between technological capabilities and legal certainty, ensuring that algorithmic governance in Indonesia remains subject to human rights principles, administrative transparency, and distributive justice.